Fourth Five-Year Plan Tamil Nadu Draft Annual Plan for 1972-73 - Planning Commission (Planning Commission, 1972)
Name of The Project With Brief Description and Location.—The Parambikulam-Aliyar Project Is A Multi-Purpose and Multi-Valley Project Which Contemplates Utilisation of Water and Power Resources of The Inter-State Rivers In The Western Ghats of India For The Benefit of Tamil Nadu and Kerala States. The Project Envisages Irrigation Facilities To An Extent of 2,40,000 Acres In Pollachi, Udumalpet, Palladam and Dharapuram Taluks of Coimbatore District and To Stabilise, Irrigation Supplies To Chittur Area of Kerala State and To Generate Power With An Installed Capacity of 1,85,000 K.W.
Finance Department, Government of Tamil Nadu